Hubungan Antara Kadar Glukosa Darah dan Daya Tahan Atlet Sepak Takraw - Arfandi Akkase; Lela Santika (Journal Physical Health Recreation (JPHR), 2022)
This study addresses the relationship between blood glucose level and the stamina of sepak takraw athletes. Eight sepak takraw athletes in Sidrap regency were involved in this study. Data in this study were analyzed using a descriptive analysis technique and a set of test including normality, correlation, and regression. The results of correlation test generate a positive correlation between blood glucose level and stamina with 0.000 significance level. In the meantime, regression analysis in the hypothesis test indicates significant correlation between blood glucose level and the stamina of sepak takraw athletes in Sidrap South Sulawesi (β = 0.953, To = 7.744, and P= 0,000<0,005).